The Pengaruh Harga Tiket Tarif Khusus, Kualitas Layanan Petugas, dan Fasilitas Fisik Stasiun Terhadap Keputusan Penggunaan Transportasi Kereta Api - Hasanah, Inggrit Aulia Wati; Iriani, Sri Setyo (Universitas Negeri Surabaya, 2024)
Trains have many enthusiasts, but currently competitive competition with bus transportation can cause consumers to switch to using this transportation. This study aims to determine and analyze the effect of special fare ticket prices, officer service quality, and station physical facilities on decisions to use train transportation services. The research methodology used is quantitative research with a survey approach using non-probability sampling techniques. Data was taken using a purposive sampling method of 200 samples. The data analysis technique used is multiple linear regression with SPSS (Statistical Package for Social Sciences) version 26. The results showed that the price of special fare tickets and the quality of station officer services had a significant positive effect on purchasing decisions, while the station's physical facilities had a significant negative effect on train usage decisions. Special fare ticket prices, officer service quality, and station physical facilities simultaneously influence train usage decisions. The practical implication of these findings is the importance of setting affordable special fare ticket prices to increase the use of rail transportation. In addition, improving the quality of station staff service, including speed of service, a sense of security, and a friendly attitude, can help attract more passengers.